1995
DOI: 10.2307/3870127
|View full text |Cite
|
Sign up to set email alerts
|

Disease Resistance Conferred by Expression of a Gene Encoding H 2 O 2 -Generating Glucose Oxidase in Transgenic Potato Plants

Abstract: Plant defense responses to pathogen infection involve the production of active oxygen species, including hydrogen peroxide (H2O2). We obtained transgenic potato plants expressing a fungal gene encoding glucose oxidase, which generates H2O2 when glucose is oxidized. H2O2 levels were elevated in both leaf and tuber tissues of these plants. Transgenic potato tubers exhibited strong resistance to a bacterial soft rot disease caused by Erwinia carotovora subsp carotovora, and disease resistance was sustained under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
4
10

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 30 publications
7
112
4
10
Order By: Relevance
“…1). This assumption is supported by the finding that heterologous expression of an apoplastic Glc oxidase, which causes constitutively enhanced H 2 O 2 levels, confers strongly enhanced E. carotovora resistance to potato tubers (Wu et al, 1995). However, other factors that might also contribute to the improved E. carotovora resistance should also be kept in mind.…”
Section: Aatp1(st)mentioning
confidence: 93%
“…1). This assumption is supported by the finding that heterologous expression of an apoplastic Glc oxidase, which causes constitutively enhanced H 2 O 2 levels, confers strongly enhanced E. carotovora resistance to potato tubers (Wu et al, 1995). However, other factors that might also contribute to the improved E. carotovora resistance should also be kept in mind.…”
Section: Aatp1(st)mentioning
confidence: 93%
“…A role for H,O, as an antimicrobial agent (Kim et al, 1988;Wu et al, 1995), a substrate for lignin synthesis (Gross et al, 1977), and a signal molecule for the hypersensitive cell death response (Levine et al, 1994), phytoalexin accumulation (Edwards et al, 1991;Guo et al, 1993), and SA biosynthesis (Leon et al, 1995) has already been demonstrated. But ROI levels must be controlled to avoid damage to the surrounding noninvaded tissue whose viability may be required for the coordinated defense response.…”
Section: Effects Of If On the Activities Of Antioxidant Enzymes And Lmentioning
confidence: 99%
“…One of the first differences is the greater increase in reactive oxygen intermediates observed during an incompatible interaction (Keppler et al, 1989;Orlandi et al, 1992). This oxidative burst may kill the pathogen directly (Keppler et al, 1989;Wu et al, 1995) or limit its spread by killing infected plant cells (Greenberg et al, 1994) and inducing cross-linkage of cell wall proteins (Bradley et al, 1992;Brisson et al, 1994). During an incompatible interaction, cell walls are also strengthened through increased deposition of hydroxy-Pro-rich glycoproteins (Showalter et al, 1985), callose (Parker et al, 1993), and lignin (Moerschbacher et al, 1990).…”
mentioning
confidence: 99%